Population survival from childhood cancer in Britain during 1978-2005 by eras of entry to clinical trials. - Stiller, C; Kroll, M; Pritchard-Jones, K (2012)
BACKGROUND: Inclusion in clinical trials is generally viewed as best practice for most newly diagnosed childhood cancers, but the impact on population-based survival has rarely been examined. PATIENTS AND METHODS: The population-based data were analysed for 25 853 children (66% of all registered childhood cancers) diagnosed in Britain during 1978-2005 with acute lymphoblastic leukaemia (ALL), acute myeloid leukaemia (AML), Hodgkin lymphoma, non-Hodgkin lymphoma, medulloblastoma, neuroblastoma, Wilms tumour, hepatoblastoma, osteosarcoma, Ewing sarcoma, rhabdomyosarcoma and germ-cell tumours. The Kaplan-Meier survival curves were compared by log-rank tests. Time trends were analysed by Cox regression. Separate analyses were done for children with ALL, medulloblastoma and neuroblastoma according to clinically relevant age thresholds. RESULTS: Survival increased significantly during 1978-2005 for every diagnostic category; the annual reduction in risk of death ranged from 2.7% (rhabdomyosarcoma) to 12.0% (gonadal germ-cell tumours). Survival increased steadily between trial eras for ALL (age 1-14 years) and neuroblastoma (age 1-14 years), but changed little since the mid-1980s for medulloblastoma (age 0-2 years), osteosarcoma or Ewing sarcoma. CONCLUSIONS: Changes in survival between trial eras parallel those reported by the relevant clinical trials. The increasing level of participation in trials, facilitated by the organisation of specialist care, has underpinned the substantial improvements in survival seen at the population level.